2022
DOI: 10.3390/ijerph192215063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Asymmetries and Functional Autonomy in Older Chilean Adults

Abstract: The objectives of this study were: (a) to determine asymmetries, both lower limb (LL) and upper limb (UL), in Chilean older adults, and (b) to relate asymmetries to FA in both LL and UL. Forty-one older adults voluntarily participated in this study (mean ± standard deviation [SD]: age 72.0 ± 8.0 years, LL asymmetries 13.78 ± 14.87%, UL asymmetries 10.70 ± 8.85%, FA 40.35 ± 16.26 points). The variables were: (1) asymmetries of LL and UL, assessed through a force platform and handgrip, respectively; (2) FA, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…This protocol consists of five functional tests: (a) put on and take off a T‐shirt (PTS), (b) stand up from the sitting position (SSP), (c) stand up from the prone position (SPP), (d) walk 10 m (W10 m), and (e) sit and get up from the chair and move around the house (SCMA), all of them evaluated in seconds (s) (Figure 1). The five functional tests are described by Huerta Ojeda et al 31 The results of the five tests are then used to calculate the score point of the GDLAM index of autonomy (GI) using the following formula 28 : GI=[(PTS+SSP+SPP+normalW100.25emnormalm)×2]+SCMA]/4. $\text{GI}=[(\text{PTS}+\text{SSP}+\text{SPP}+{\rm{W}}10\,{\rm{m}})\times 2]+\text{SCMA}]/4.$…”
Section: Methodsmentioning
confidence: 99%
“…This protocol consists of five functional tests: (a) put on and take off a T‐shirt (PTS), (b) stand up from the sitting position (SSP), (c) stand up from the prone position (SPP), (d) walk 10 m (W10 m), and (e) sit and get up from the chair and move around the house (SCMA), all of them evaluated in seconds (s) (Figure 1). The five functional tests are described by Huerta Ojeda et al 31 The results of the five tests are then used to calculate the score point of the GDLAM index of autonomy (GI) using the following formula 28 : GI=[(PTS+SSP+SPP+normalW100.25emnormalm)×2]+SCMA]/4. $\text{GI}=[(\text{PTS}+\text{SSP}+\text{SPP}+{\rm{W}}10\,{\rm{m}})\times 2]+\text{SCMA}]/4.$…”
Section: Methodsmentioning
confidence: 99%
“…The unit of measurement for all tests is time in s. A digital stopwatch Casio1 HS-70W-1 model (Tokyo, Japan) was used for the time evaluation of the five functional tests. The five functional tests were described by Huerta Ojeda et al [33]:…”
Section: Gdlam's Protocolmentioning
confidence: 99%
“…Concerning the SSP test evaluated in the present study, our results showed a CV equivalent to 9.01% (95% CI = 7.37-11.61) and an ICC equivalent to 0.79 (95% CI = 0.64-0.89), evidencing acceptable reliability and high interday reproducibility in OW. The different SSP or similar protocols used to assess the ability to stand and sit have shown a positive association between lower limb strength and higher FA on OW [33]. In parallel, SSP, as an activity…”
Section: Stand Up From the Sitting Position (Ssp)mentioning
confidence: 99%
“…In this sense, in the research carried out by Huerta Ojeda et al FA (2022) asymmetries were determined, from muscle strength tests, of the lower and upper limbs in Chilean OP and, later, they were related to FA. At the end of the study, it is ruled out that a higher level of asymmetries in the older adults (OA) shows a lower level of FA (Huerta Ojeda et al, 2022). These antecedents show that early evaluation allowed an intervention to be correctly channeled, as well as the evidence which relates muscle strength, anthropometry, and asymmetries with FA in this segment of the Chilean population is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, in Chile there is limited information on the relationship between muscle strength levels and asymmetries in FA in OW (Huerta Ojeda et al, 2022). In this sense, in the research carried out by Huerta Ojeda et al FA (2022) asymmetries were determined, from muscle strength tests, of the lower and upper limbs in Chilean OP and, later, they were related to FA.…”
Section: Introductionmentioning
confidence: 99%